Haplogroup diversity in the Indian population using 23 Y-STRs - Pankaj Shrivastava; Muktikanta Panda; Kamlesh Kaitholia; Shivani Dixit; Ramkishan Kumawat; Hari Shankar; A. N. Sharma; Gyaneshwer Chaubey (Taylor & Francis Group, 2022)
Background A Y-STR polymorphism study is a convenient tool in molecular anthropology and forensic DNA analysis. Aim Through standard ethical procedures, the proposed study explored the genetic scenario in male lineage in Madhya Pradesh, a central Indian state, by Y-STR genotyping and haplogroup studies. Subjects and methods Five hundred and eleven unrelated male blood samples were directly amplified, and fragment separation was done using capillary electrophoresis to generate a Y-STR profile for 23 forensic relevant markers through PowerPlex® Y 23 multiplex system. The different statistical methods were applied for studying the forensic and genetics parameters. Subsequently, population comparison was performed by AMOVA, PCoA, and MDS plot, and Haplogroups were predicted with Whit Athey's haplogroup predictor tool. Conclusion These data represented the potential value of the PowerPlex® Y-23 multiplex system for the forensic and human genetics application in the population of Madhya Pradesh, India. Simultaneously the Haplogroup analysis revealed information about the multi-geographic origin as well as multi-ethnic genetic affinities of the Madhya Pradesh population.